CULTIVATING RESILIENCE: MINDFULNESS, ACCEPTANCE, AND GRATITUDE-BASED INTERVENTIONS IN PSYCHOTHERAPY FOR IMMIGRANTS - George Gharibian (PEOPLE: International Journal of Social Sciences, 2025)
Immigrants and refugees often face profound challenges and losses that are difficult to overcome. Feelings of isolation, the loss of homeland, disconnection from family and friends, and a lack of belonging are some of the obstacles that can lead to stress or even despair. Additionally, therapeutic approaches that fail to account for cultural differences, as well as the unique expectations and sense of agency of immigrants and refugees, may result in less effective treatment outcomes. However, therapies based on acceptance, mindfulness, and gratitude have demonstrated an ability to bridge cultural gaps and empower individuals to regain a sense of agency while addressing the mental health challenges linked to their immigration experiences. These strength-based interventions align well with various therapeutic models, including humanistic and existential therapies, which serve as two examples of psychotherapy approaches that can effectively incorporate acceptance, mindfulness, and gratitude. A point of caution is that gratitude-based approaches do not overlook the suffering of immigrants. Instead, they help reframe their experiences as opportunities, enabling them to tap into their resilience and cultivate self-compassion. This paper will explore specific treatment strategies using acceptance, mindfulness, and gratitude to help immigrants and refugees navigate the mental health difficulties they face.